2016
DOI: 10.1007/s11999-016-4741-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients After Chondrosarcoma Treatment Have Age-appropriate Bone Mineral Density in the Long Term?

Abstract: BackgroundIn long-term survivors of osteosarcoma and Ewing sarcoma treated with the addition of radio- and chemotherapy, low bone mineral density (BMD) and fractures have been observed, presumably resulting from these adjuvants. Because patients with chondrosarcoma usually are not treated with conventional adjuvant treatment, observation of low BMD in patients with chondrosarcoma presumably would be the result of other mechanisms. However, BMD in patients with a history of chondrosarcoma has not been well char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Our study also confirm this finding as majority of the patients in our study were found to be between the ages of 20 to 50 years of age and only 2 patients were seen below the age of 20 years. Similar findings were seen in the studies conducted by Gerhard M. Hobusch et al and Welkerling H et al [18,19] The most common clinical presentation of Chondrosarcoma consist of local swelling which may increase slowly or rapidly depending upon the grade of tumor. A high grade tumor is expected to grow rapidly and chances of recurrence after excision and distant metastasis is more in high grade tumor.…”
Section: Discussionsupporting
confidence: 87%
“…Our study also confirm this finding as majority of the patients in our study were found to be between the ages of 20 to 50 years of age and only 2 patients were seen below the age of 20 years. Similar findings were seen in the studies conducted by Gerhard M. Hobusch et al and Welkerling H et al [18,19] The most common clinical presentation of Chondrosarcoma consist of local swelling which may increase slowly or rapidly depending upon the grade of tumor. A high grade tumor is expected to grow rapidly and chances of recurrence after excision and distant metastasis is more in high grade tumor.…”
Section: Discussionsupporting
confidence: 87%
“…Chondrosarcoma is a malignant bone tumor but is uncommon in children. The standard treatment consists of a wide resection or aggressive curettage, only for selected lowgrade extremity chondrosarcomas, and is usually not followed by conventional adjuvant treatment [58]. Very little data exist on effects on bone health.…”
Section: Part Ii: Bone Health In Ccss Osteopenia/osteoporosis In Ccssmentioning
confidence: 99%
“…At present, the main treatment method for CHS is surgical resection. Thus, it is of great importance to elucidate the underlying mechanism of CHS to develop a novel therapeutic method for patients with CHS (1,19). Due to their extensive effects on cell proliferation, differentiation, apoptosis, and drug resistance, miRNAs have been revealed to be widely involved in the progression of a number of tumors (20,21).…”
Section: Discussionmentioning
confidence: 99%